Does whole-body cryotherapy improve vertical jump recovery following a high-intensity exercise bout? - Vieira A (Open Access Journal of Sports Medicine, 2015)
Amilton Vieira,1 Martim Bottaro,1 Joao B Ferreira-Junior,1,4 Carlos Vieira,1 Vitor A Cleto,1 Eduardo L Cadore,2 Herbert G Simões,3 Jake Do Carmo,1 Lee E Brown5 1College of Physical Education, University of Brasília, Brasília, 2College of Physical Education, Federal University of Rio Grande do Sul (UFRGS), Porto Alegre, 3College of Physical Education, Catholic University of Brasília, Brasília, 4Federal Institute of Triângulo Mineiro, Paracatu, Brazil; 5Department of Kinesiology, California State University, Fullerton, CA, USA Abstract: Whole-body cryotherapy (WBC) has been used as a recovery strategy following different sports activities. Thus, the aim of the study reported here was to examine the effect of WBC on vertical jump recovery following a high-intensity exercise (HIE) bout. Twelve trained men (mean ± standard deviation age = 23.9±5.9 years) were randomly exposed to two different conditions separated by 7 days: 1) WBC (3 minutes of WBC at −110°C immediately after the HIE) and 2) control (CON; no WBC after the HIE). The HIE consisted of six sets of ten repetitions of knee extensions at 60° · s−1 concentric and 180° · s−1 eccentric on an isokinetic dynamometer. The vertical jump test was used to evaluate the influence of HIE on lower extremity muscular performance. The vertical jump was performed on a force platform before HIE (T1) and 30 minutes after (T2) the WBC and CON conditions. As a result of HIE, jump height, muscle power, and maximal velocity (Vmax) had significant decreases between T1 and T2, however no significance was found between the WBC and CON conditions. The results indicate that one session of WBC had no effect on vertical jump following an HIE compared with a CON condition. WBC may not improve muscle-function (dependent on stretch-shortening cycle) recovery in very short periods (ie, 30 minutes) following HIE. Keywords: functional performance, muscular recovery, countermovement jump